2021
DOI: 10.3390/nu13103361
|View full text |Cite
|
Sign up to set email alerts
|

Consumption of Food Supplements during the Three COVID-19 Waves in Poland—Focus on Zinc and Vitamin D

Abstract: Food supplements (FS) are a concentrated source of vitamins, minerals, or other ingredients with nutritional or other physiological effects. Due to their easy availability, widespread advertising, and sometimes low price, increased consumption of this group of preparations has been observed. Therefore, the aim of the study was to assess the knowledge and intake of FS during the COVID-19 pandemic in Poland, with particular reference to FS containing zinc and vitamin D. It was noted that both of the above ingred… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
34
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(41 citation statements)
references
References 26 publications
6
34
1
Order By: Relevance
“…The present study has not confirmed the hypothesis that the COVID-19 pandemic increased vitamin D consumption in surveyed individuals. Interestingly, Puścion-Jakubik et al demonstrated that a significantly greater percentage of Polish respondents declared not taking food supplements with zinc and vitamin D during the first wave of the COVID-19 pandemic [26]. In many countries, an evaluated interest in diet supplementation during the COVID-19 pandemic was found [27][28][29].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The present study has not confirmed the hypothesis that the COVID-19 pandemic increased vitamin D consumption in surveyed individuals. Interestingly, Puścion-Jakubik et al demonstrated that a significantly greater percentage of Polish respondents declared not taking food supplements with zinc and vitamin D during the first wave of the COVID-19 pandemic [26]. In many countries, an evaluated interest in diet supplementation during the COVID-19 pandemic was found [27][28][29].…”
Section: Discussionmentioning
confidence: 99%
“…It may suggest that women are more worried about their health and more interested in pro-health prophylaxis than men. The Polish Economic Institute notified that the worth of the food supplements market was estimated to amount to 4.4 billion PLN in 2017 and over 70% of Poles used food supplements [26,30]. It seems that cognizance in differences between medications and supplements, side effects, and their possible interaction with medications has increased.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Research conducted thus far in Poland and in the world has shown the positive effect of the COVID-19 pandemic on health-promoting behavior in humans. The above behaviors have been manifested by an increase in the use of appropriate dietary supplements, such as vitamin C or D [15], and OTC drugs with anti-viral and immunostimulating properties [16], the use of a balanced diet [17], and adherence to the restrictions imposed by the government [10].…”
Section: Introductionmentioning
confidence: 99%
“…Many during the pandemic turned to seeking additional protections against SARS-CoV-2 and COVID-19 via the use of dietary supplement and nutraceuticals [ 11 ]. In this Special Issue, Puscion-Jakubik et al examined the consumption of food supplements during the first three COVID-19 waves in Poland (spring and autumn 2020 and winter 2021) [ 12 ]. Approximately 300 participants responded to each questionnaire, with 80% of the respondents being women, the mean age was approximately 29 ± 10 years, and approximately 50% having medical or related education, and nearly all either working in an office or studying as a student.…”
mentioning
confidence: 99%